2022
DOI: 10.1021/acsanm.2c02196
|View full text |Cite
|
Sign up to set email alerts
|

Benzaldehyde Lyase Kinetic Improvements, Potential Channeling to Alcohol Dehydrogenase, and Substrate Scope when Immobilized on Semiconductor Quantum Dots

Abstract: Cell-free enzymatic cascades have gained increasing interest as one-pot reaction strategies to synthesize complex organic molecules in an efficient, selective, and environmentally sustainable manner. Enzyme immobilization onto nanoparticle surfaces can potentially allow them to benefit from stabilization, localized kinetic enhancement, and to access substrate channeling phenomena in the case of coupled activity. Here, we analyze the activity of benzaldehyde lyase (Bal) when assembled on semiconductor quantum d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 66 publications
2
17
0
Order By: Relevance
“…2C–F. As noted repeatedly, 27,29,33 QD samples lacking GDH present were quite monodisperse in comparison, see ESI Fig. S1 †.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…2C–F. As noted repeatedly, 27,29,33 QD samples lacking GDH present were quite monodisperse in comparison, see ESI Fig. S1 †.…”
Section: Resultssupporting
confidence: 65%
“…, dimers or tetramers) and display multiple pendant (His) 6 at their termini, it has been repeatedly confirmed that the QDs and enzymes, whether present individually or as part of a multienzyme cascade, will crosslink into nanoclusters by what appears to be a classical diffusion-limited aggregation (DLA) process. 27–29,33,56 This process also inherently dictates that the final size and structure of the resultant nanoclusters will depend on a complex interplay of the QD and enzyme(s) concentrations present along with their size and shape and the reaction volume amongst other variables. This complex multivariable dependency means that, although the nanoclusters will form, their final size and shape cannot be predicted or controlled.…”
Section: Resultsmentioning
confidence: 99%
“…Our prior efforts looked to understand the catalytic enhancements (e.g., 2–50× improvements in k cat ) observed in enzymes attached to NPs such as semiconductor quantum dots (QDs) or gold NPs (AuNPs) 52 54 . Work with amylase, glucokinase, phosphotriesterase, β -galactosidase, benzaldehyde lyase (Bal), alkaline phosphatase, and lactate dehydrogenase (LDH) revealed that enhancements arose from localized nanoenvironment and interfacial effects at the NP-solvent boundary, which served to alleviate key rate-limiting steps (e.g., enzyme-product release or k off ) and also from stabilizing enzyme structures 55 61 . Moreover, enhancements were often dependent on NP size, with smaller diameter materials generally favoring catalytic increases 52 .…”
Section: Introductionmentioning
confidence: 99%
“…Detailed experiments, along with simulations, confirmed intermediate channeling between the QD-colocalized enzymes in the clusters 55 . Moreover, when Bal was recently paired with an alcohol dehydrogenase in similarly cross-linked QD enzyme clusters, their coupled enzymatic flux increased 50% despite the two enzymes differing by >10 4 in catalytic rate and by three orders of magnitude in their respective Michaelis constant, K M 61 .…”
Section: Introductionmentioning
confidence: 99%
“…The surface functionalized nanofiber membranes were examined as a support material for enzyme immobilization, which increased the storage stability and reusability, and a novel amylase immobilized poly(vinyl alcohol) (PVA) nanofibers were developed [ 143 ]. Nanoparticle immobilization has contributed greatly to the biocatalysis of enzymes in different functional forms [ 144 ]. In addition to the immobilization of enzymes on substrates by various methods, the self-assembly of enzymes has also been developed, including assembly between different enzymes or with other catalytically active catalysts.…”
Section: One-step Synthesis For Enzyme Assembliesmentioning
confidence: 99%